Integrating Public Relations and Islamic Marketing Strategies for Enhancing Brand Trust and Consumer Engagement among SMEs in Sokoto State, Nigeria - Saidu, Basiru (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2025)
Introduction: Small and Medium Enterprises (SMEs) in Sokoto State play a vital role in local economic development. However, limited research has examined how they integrate Public Relations (PR) and Islamic marketing principles to build consumer trust and strengthen brand reputation. This study addresses this gap by exploring how SMEs apply ethical communication rooted in Islamic values within their marketing and Public Relations practices. Relationship Marketing Theory, the Two-Way Symmetrical Communication Model, and the Islamic Business Ethics Framework guide the study. Research Methods: The study employed a qualitative research design, utilizing in-depth interviews with owners of Small and Medium Enterprises, Public Relations practitioners, and Islamic scholars. Results: The findings revealed that while SME operators value honesty, fairness, and transparency, most lack formal Public Relations strategies that align with Islamic ethical principles. Conclusion: The study concludes that integrating Public Relations with Islamic marketing ethics enhances consumer trust and supports long-term business growth. The study contributes theoretically by linking Islamic ethics with modern communication models and practically by recommending culturally grounded Public Relations capacity-building initiatives.